The interplay of birth weight, dopamine receptor D4 gene (DRD4), and early maternal care in the prediction of disorganized attachment at 36 months of age. (6th October 2015) - Wazana, Ashley; Moss, Ellen; Jolicoeur-Martineau, Alexis; Graffi, Justin; Tsabari, Gal; Lecompte, Vanessa; Pascuzzo, Katherine; Babineau, Vanessa; Gordon-Green, Cathryn; Mileva, Viara; Atkinson, Leslie; Minde, Klaus; et al.
Abstract: Disorganized attachment is an important early risk factor for socioemotional problems throughout childhood and into adulthood. Prevailing models of the etiology of disorganized attachment emphasize the role of highly dysfunctional parenting, to the exclusion of complex models examining the interplay of child and parental factors. Decades of research have established that extreme child birth weight may have long-term effects on developmental processes. These effects are typically negative, but this is not always the case. Recent studies have also identified the dopamine D4 receptor ( DRD4 ) as a moderator of childrearing effects on the development of disorganized attachment. However, there are inconsistent findings concerning which variant of the polymorphism (seven-repeat long-form allele or non–seven-repeat short-form allele) is most likely to interact with caregiving in predicting disorganized versus organized attachment. In this study, we examined possible two- and three-way interactions and child DRD4 polymorphisms and birth weight and maternal caregiving at age 6 months in longitudinally predicting attachment disorganization at 36 months. Our sample is from the Maternal Adversity, Vulnerability and Neurodevelopment project, a sample of 650 mother–child dyads. Birth weight was cross-referenced with normative data to calculate birth weight percentile. Infant DRD4 was obtained with buccal swabs and categorized according to the presence of the putative allele seven repeat. Macroanalytic and microanalytic measures of maternal behavior were extracted from a videotaped session of 20 min of nonfeeding interaction followed by a 10-min divided attention maternal task at 6 months. Attachment was assessed at 36 months using the Strange Situation procedure, and categorized into disorganized attachment and others. The results indicated that a main effect for DRD4 and a two-way interaction of birth weight and 6-month maternal attention (frequency of maternal looking away behavior) and sensitivity predicted disorganized attachment in robust logistic regression models adjusted for social demographic covariates. Specifically, children in the midrange of birth weight were more likely to develop a disorganized attachment when exposed to less attentive maternal care. However, the association reversed with extreme birth weight (low and high). The DRD4 seven-repeat allele was associated with less disorganized attachment (protective), while non–seven-repeat children were more likely to be classified as disorganized attachment. The implications for understanding inconsistencies in the literature about which DRD4 genotype is the risk direction are also considered. Suggestions for intervention with families with infants at different levels of biological risk and caregiving risk are also discussed.